Mechanisms driving woody encroachment in the tallgrass prairie: an analysis of fire behavior and physiological integration - Killian, Paul D. (Kansas State University, 2012)
Woody encroachment has altered the vegetative structure of grasslands worldwide and represents a potentially irreversible shift in grassland dynamics and biodiversity. Clonal woody species appear to be one of the greatest contributors to the shift from graminoid to woody dominance in the tallgrass prairie. Part of the high success rate of clonal species may be attributed to an ability to circumvent recruitment filters through the integration of environmental heterogeneity and acropetal translocation of resources from mother to daughter ramets. The clonal shrub Cornus drummondii persists in a tension zone of the graminoid-dominated tallgrass prairie, where the dominance structure is primarily maintained through the direct and indirect effects of fire. The competitive displacement of native herbaceous vegetation associated with the establishment and expansion of C. drummondii causes a major alteration in the fuel dynamics responsible for the propagation and sustainment of fire, potentially contributing to biofeedback mechanisms that facilitate shrub expansion. The goal of this research was to quantify fire behavior parameters (temperature, intensity, rate of spread, and heat flux) in relation to C. drummondii invasions and to test physiological integration as a mechanism driving encroachment, using manipulation experiments at the Konza Prairie Biological Station. We observed a significant decrease in fireline intensity associated with the encroachment of C. drummondii, which was amplified by the effects of stem density and shrub island area. This alteration in fire behavior also led to reduced heat flux at stems within shrub islands, reducing the likelihood of tissue necrosis and top-kill. With additional fuel, temperatures and fire intensities were higher, similar to open grasslands. In severing rhizomes, and effectively severing the integration of clonal ramets, we observed a higher risk of mortality of daughter ramets. These rhizome severed ramets were more water stressed, had lower photosynthetic rates, and lower woody and foliar biomass production. These results indicate that C. drummondii significantly alters fire behavior, releasing ramets from the fire trap of successive top-killing, while the integration of intraclonal ramets allows daughter ramets to survive mid-summer drought and increases the likelihood of successful establishment and further clonal reproduction.
Keywords: Cornus drummondii; Fire behavior; Physiological integration; Woody encroachment; Biology (0306); Ecology (0329)